THE FORMATIVE DIMENSION OF THE GRADUATE ASSESSMENT PROCESS: CONSIDERATIONS ON THE NEW CAPES’ ASSESSMENT MODEL - Oliveira, Terezinha [UNESP]; Stecanela, Nilda; Boufleuer, José Pedro (FapUNIFESP (SciELO), 2023)
The article considers the postgraduate evaluation model implemented by the Coordination for the Improvement of Higher Education Personnel Capes in the four-year period 2017-2020, highlighting its formative character expressed in its different requirements, items, and indicators. In a historical shift in the evaluation process, previously centered on quantitative data and privileging what became known as the productivist evaluation bias, the new evaluation model, strongly based on qualitative indicators, without neglecting quantitative data, emphasizes the pedagogical character of the programs, considering its internal dynamics and its orientation towards the training of competent staff to work in research, aiming at producing an impact on society and its institutions with a view to improving people’s lives. To support this reading, and bearing in mind the specificities of the education area, this article details aspects of the new assessment form, especially regarding the items “training” and “impact on society”, highlighting the pedagogical-formative dimensions of the programs, as well as the more general sense of human formation that is expressed in an understanding of co-responsible citizenship and orientation towards the construction of a life in common. On the other hand, it makes considerations about the new demand placed on programs that need to produce narratives of themselves in descriptive reports to be sent to Capes, which requires a new level of reflexivity about their processes and purposes.
LA DIMENSIÓN FORMATIVA DEL PROCESO DE EVALUACIÓN DE LOS CURSOS DE POSGRADO: CONSIDERACIONES SOBRE EL NUEVO MODELO DE EVALUACIÓN DE LA CAPES
A DIMENSÃO FORMATIVA DO PROCESSO DE AVALIAÇÃO DA PÓS-GRADUAÇÃO: CONSIDERAÇÕES SOBRE O NOVO MODELO DE AVALIAÇÃO DA CAPES
Keywords: Capes; Education; Human formation; Impact on society; Postgraduate evaluation